Childhood Trauma Is Nominally Associated With Elevated Cortisol Metabolism in Severe Mental Disorder - Aas, Monica; Ueland, Torill; Inova, Amina; Melle, Ingrid; Andreassen, Ole A.; Steen, Nils Eiel (Frontiers in Psychiatry, 2020)
Objective Individuals exposed to childhood trauma display longstanding modifications of the Hypothalamic–Pituitary–Adrenal (HPA) axis, as well as cognitive impairments. Schizophrenia spectrum disorder (SZ) and bipolar disorders (BD) are characterised by higher prevalence of childhood trauma, abnormal HPA axis, and cognitive dysfunction. Elevated cortisol metabolism was recently demonstrated in both disorders. However, it is yet to be established if childhood adversity is associated with cortisol metabolism in this population, and how this may be associated with cognitive function. Methods One-hundred-and-fourteen participants with a DSM-IV SZ or BD diagnosis took part in the study. Diagnoses were evaluated by the Structured Clinical Interview for DSM-IV Axis I disorders (SCID-I). Estimated cortisol metabolizing activity (5α-reductase and 5β-reductase) was assessed by urinary free cortisol, and metabolites. All patients underwent cognitive assessment and completed the Childhood Trauma Questionnaire. Results Estimated 5β-reductase activity was elevated in participant with childhood physical abuse (r = 0.26, p = 0.005). After adjusting for age, sex and diagnosis, physical abuse was still nominally associated with elevated 5β-reductase. Moreover, only high 5α-reductase activity was negatively correlated with working memory and executive performance (r = −0.23, p = 0.01; r = −0.19, p = 0.05, respectively), however this disappeared after adjusting for age, sex and diagnosis. Cortisol metabolism did not mediate the association between childhood trauma and cognitive function. Conclusions Our study indicates that childhood physical abuse is associated with elevated cortisol metabolism (5β-reductase) in adults with a SZ or BD disorder. However, our study did not support cortisol metabolism as a mediator between childhood trauma experiences and cognitive function within these disorders.